1983
DOI: 10.3168/jds.s0022-0302(83)81789-5
|View full text |Cite
|
Sign up to set email alerts
|

Yield and Fertility Relationships in Dairy Cattle

Abstract: Measures of yield and fertility were obtained from breeding receipts of artificial insemination and records of test-day yield. Estimates of heritability were by Henderson Method 3, maximum likelihood, and restricted maximum likelihood. Heritabilities for measures of yield varied, but most were within the range of earlier estimates. Measures of fertility had heritabilities from 0 to .03. Alternative upper bounds were placed on days open, number of services, and service period, and always the measure with the le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

16
52
5
13

Year Published

1989
1989
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 155 publications
(86 citation statements)
references
References 30 publications
16
52
5
13
Order By: Relevance
“…Mean heritability estimates were in the same range as those found in several studies from various populations (Hansen et al, 1983;Campos et al, 1994;Conzàlez-Recio and Alenda, 2005;Liu et al, 2008;Sewalem et al, 2010;Ghiasi et al, 2011). Ghiasi et al (2011) reported 0.074 ± 0.004, 0.076 ± 0.004, 0.044 ± 0.004, 0.058 ± 0.005, and 0.046 ± 0.004 for CI, DO, FIC, DFI, and NI, respectively, using the same model.…”
Section: Discussionsupporting
confidence: 70%
“…Mean heritability estimates were in the same range as those found in several studies from various populations (Hansen et al, 1983;Campos et al, 1994;Conzàlez-Recio and Alenda, 2005;Liu et al, 2008;Sewalem et al, 2010;Ghiasi et al, 2011). Ghiasi et al (2011) reported 0.074 ± 0.004, 0.076 ± 0.004, 0.044 ± 0.004, 0.058 ± 0.005, and 0.046 ± 0.004 for CI, DO, FIC, DFI, and NI, respectively, using the same model.…”
Section: Discussionsupporting
confidence: 70%
“…Estimates averaged over data sets and different analyses were .10 for DO and .19 for DFI when individual estimates were averaged by weighting by the number of sires in data sets. In other studies where both DFI and DO have been included, heritability of DFI is commonly tbund to be larger than that of DO, with estimates averaging about .04 and .02 for DFI and DO, respectively (2,10,17,18)…”
Section: Heritabilitiesmentioning
confidence: 99%
“…High milk production has long been known to be associated with poor fertility, either because of genetic or environmental reasons (2,6,7,8,10,15,19,23,26). The same studies, however, have shown that heritability of breeding efficiency is generally below .05.…”
Section: Introductionmentioning
confidence: 99%
“…Although some studies from field data show an antagonistic relationship between milk yield and fertility in dairy cows (4,5,9,21,25,28) and a complementary relationship among measures of fertility from breeding heifers and measures of their first lactation production (8,17,18), "more knowledge is needed before the genetic relationships are known well enough to determine what, if any, changes are needed in selection practice" (7). Calving interval (CI), influenced by all fertility traits, can be used to estimate the genetic covariance between production and reproduction.…”
Section: Introductionmentioning
confidence: 99%